Impact of a Langmuir Probe on Turbulence Measurements in the Scrape‐Off‐Layer of Tokamaks. Issue 4 (June 2014) - Colin, C.; Tamain, P.; Ghendrih, P.; Schwander, F.; Serre, E.
Abstract An issue for Langmuir probe measurements of SOL turbulence concerns the impact of the probe itself on plasma transport. The aim of this paper is to investigate this issue with a synthetic reconstruction of Langmuir probe measurements by inserting a synthetic probe into a 2D fluid SOL turbulence code. The effect of a biased probe is analysed as a function of its size. It is shown that the probe creates a transport barrier whose effect is non‐local and affects the current's circulation in the plasma. The plasma density is depleted by the presence of the probe as well as the electrostatic potential. A strong impact on turbulence can also be observed. Such observations imply that the probed turbulence can differ significantly from the probe‐free turbulence. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)